Development of Game-based Learning Media for Early Childhood Animal Recognition - Tri Lestariningsih; Hendrik Kusbandono; Angger Binuko Paksi; Yosi Afandi; Ikhwan Baidlowi Sumafta (PT FORMOSA CENDEKIA GLOBAL, 2023)
Cognitive learning activities through the introduction of animals in Early Childhood (AUD) have a very important role in developing all children's potential. One of them is the potential intelligence of children. AUD is a pretty good stage for training the brain of a child, where they will be more interested and active when they see a game or such that contains a lot of animation and sound. With the existence of game-based animal recognition learning media, it will be an interesting thing for early childhood, namely kindergarten, as well as teachers when interacting and conducive to learning. This learning medium contains several learning points and games that train children's cognitive abilities. There is a learning menu to recognize the name of the animal and its voice, then the game composes the word and guesses the illustration image of the animal, as well as the support of singing videos about animals given by the teacher to children. Game-based learning media is built using constructivism, using Luther Sutopo's method. The result of this research is an animal recognition learning medium for early childhood.